Comparing potassium permanganate, chlorine dioxide, and chlorine oxidation for manganese control of a volcanic island surface water treated with a conventional coagulation, sedimentation, and filtration process. Issue 31 (2nd July 2016) - Hall, Christine; LaBerge, Erica R.; Duranceau, Steven J.
Abstract: A comparison of the effectiveness of potassium permanganate (KMnO4 ), chlorine dioxide (ClO2 ), and chlorine (Cl2 ) oxidation pretreatment for manganese (Mn) control from a surface water reservoir on the volcanic island of Guam has been completed. Source water dissolved Mn content was determined to be 7.34 μg/L at a reservoir intake depth of 10 ft, 9.85 μg/L at a depth of 20 ft, 41.6 μg/L at a depth of 30 ft, and 775 μg/L at a 40 foot depth. For the intake depth of 10 ft, it was found that a ClO2 dose of 1.1 mg/L reduced Mn by an average of 98.7%, as compared to an average of 95.9% using a KMnO4 dosage of 1.75 mg/L. Cl2 was found not to reduce dissolved Mn to any extent at dosages of 1.25 mg/L. It was determined that pink water formation occurred with less than 0.5 mg/L of a permanganate overdose. Additionally, a 1.1 mg/L ClO2 dose produced an average chlorite and chlorate by-product concentration of 780–1, 080 μg/L, respectively. Results demonstrated that ClO2 would be the preferred oxidant for Mn control as compared to KMnO4 or Cl2 for the volcanic water supply evaluated in this study. The research also verified that a 0.10-micron filter produced more accurate dissolved Mn results than the standard method use of 0.45-micron filter in laboratory procedures.